Scientific Collaboration at National Institute of the Atlantic Forest (Brazil) on Scopus Database: Analysis of Institutional Domain - Freitas, Juliana Lazzarotto; Rosas, Fabio Sampaio (Frontiers in Research Metrics and Analytics, 2020)
Domain analysis by means of scientific collaboration enables evidencing aspects that are involved in the establishment of relationships between researchers and institutions, such as the influence of institutional management models for the development of collaborative networks. It aims to analyze the scientific collaboration network of the National Institute of the Atlantic Forest (INMA), a research unit currently affiliated to the Brazilian Ministry of Science, Technology and Innovation (MCTI), formerly known as the Professor Mello Leitão Museum of Biology (MBML), in order to acknowledge the institutional research identity in its historical journey as a public institution. It is thus analyzed how co-authorship constitutes this network and what research profile it reveals. Co-authorship analysis is adopted, as well as the analysis of administrative documents with the survey and categorization of employees, regarding their types of ties to the institution, combined with searches in the Scopus database for the corroboration of institutional affiliations. A corpus of 138 articles published by 41 researchers from 1993 to 2019 is consolidated in this base, which represents 44% of the Institute's total research collaborators. Of these 41, 92.5% have temporary links, such as scholarship holders and volunteers, with the remaining being public workers. It is recognized that the citation impact of the scientific production of scholarship holders, consigned to the Institute, is less than the citation impact of the volunteers' and public workers' production. It is evidenced that eight of the ten publications with the greatest impact and thematic prominence correspond to the field of zoology, with emphasis on herpetology and primatology. Macro-level collaborative relations are more intense with the United States, in both areas mentioned, covering 16% of the total corpus of articles in cooperation with that country. Zoology, besides its greater impact, accounts for more than half of the corpus production (65,9%).On the other hand, botany is responsible for 30,4% of the corpus, with its dispersed international cooperation in a broad variety of countries. Individual authorship articles are 57% consigned to botany. In summary, the accomplished analysis will contribute to the development of institutional domain analysis methodologies that present scientific collaboration as a basic procedure.